Persepsi Peternak Terhadap Aspek Reproduksi Ternak Kambing di Kabupaten Lombok Utara - Lalu Ahmad Zaenuri; Rodiah Rodiah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2018)
The research conducted in order to know farmer perception on goat reproduction in North Lombok District. Farmer groupswereselected by purposive random sampling. Each group represented by 10 respondents. Collected data then tabulated and quantified, interpreted and presented descriptively. The initial populations in the past 5.6 years were 243 (50 males and 193 females), currently remaining458 (340 females and 118 males) excluding those weresold. 80% of respondents know the age of doe’s at the first mating and 88.8% know oestrus signs. 67% of respondents did not know post kidding open days. 100% doe's were naturally mated. 50% respondents stated mating frequenciesfor optimum fertility rate was 1-2 times, 12% said 3-4 times and the remaining 38% did not know. Only 56.7% of respondents knew doe’slength ofpregnancy. Doe’s with twins of two or morekidding were 59.3% and single kid was 40.70%. Almost 100% of respondents know genetically superior bucks. In conclusion, on one hand the perception of respondent's on goat reproduction is relatively low, but on the other hand the goat production was relatively high. To accelerate the increase in productivity of goats in North Lombok Regency, was recommended that local goats are crossed with superior goats such as Ettawa goats or Boer goats